Experimental investigation on the dynamic response of RC flat slabs after a sudden column loss - Russell, J.M.; Owen, J.S.; Hajirasouliha, I. (Elsevier, 2015)
To prevent disproportionate collapse under an extreme loading event, a sudden column loss scenario is often used to ensure the structure has suitable robustness. This study aims to investigate experimentally the dynamic response of reinforced concrete flat slabs after a sudden column loss. Seven 1/3 scale reinforced concrete flat slabs were tested under static load increases or dynamic column removal cases with different supports removed. Reaction forces and deflections were recorded throughout, along with reinforcement strains and concrete cracking patterns. During dynamic tests, a high speed camera was used to capture the dynamic motion.